Perlindungan Hukum Kepada para Pihak Terkait Harta Bersama dalam Pembagian Aset Perkawinan Campuran Berupa Tanah dan Bangunan : Studi Putusan Mahkamah Agung Nomor 2457 K/Pdt/2020 - Muhammad Nurilham; hasim purba; Dedi Harianto (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Mixed marriages between Indonesian citizens and foreign nationals raise legal issues, particularly regarding joint property in the form of land and buildings under the nationality principle of the Basic Agrarian Law. This study analyzes the legal status of such property, legal protection for the parties and judicial considerations in Supreme Court Decision No. 2457 K/Pdt/2020. Using normative, descriptive-analytical methods with statutory and case approaches, the study finds that land ownership without a prenuptial agreement risks violating Article 21 UUPA. Legal protection is provided preventively through marital agreements and repressively through court settlements, with judges affirming equal division of jointly acquired assets.